Solution Structure of the PilZ Domain Protein PA4608 Complex with Cyclic di-GMP Identifies Charge Clustering as Molecular Readout - Judith Habazettl; Martin Allan; Urs Jenal; Stephan Grzesiek (2011)
Cyclic diguanosine monophosphate (c-di-GMP) is a ubiquitous bacterial second messenger that controls the switch from a single-cell lifestyle to surface-attached, multicellular communities called biofilms. PilZ domain proteins are a family of bacterial c-di-GMP receptors, which control various cellular processes. We have solved the solution structure of the Pseudomonas aeruginosa single-domain PilZ protein PA4608 in complex with c-di-GMP by NMR spectroscopy. Isotope labeling by 13C and 15N of both the ligand and the protein made it possible to define the structure of c-di-GMP in the complex at high precision by a large number of intermolecular and intraligand NOEs and by two intermolecular hydrogen bond scalar couplings. Complex formation induces significant rearrangements of the C- and N-terminal parts of PA4608. c-di-GMP binds as an intercalated, symmetric dimer to one side of the β-barrel, thereby displacing the C-terminal helix of the apo state. The N-terminal RXXXR PilZ domain motif, which is flexible in the apo state, wraps around the ligand and in turn ties the displaced C terminus in a loose manner by a number of hydrophobic contacts. The recognition of the dimeric ligand is achieved by numerous H-bonds and stacking interactions involving residues Arg8, Arg9, Arg10, and Arg13 of the PilZ motif, as well as β-barrel residues Asp35 and Trp77. As a result of the rearrangement of the N and C termini, a highly negative surface is created on one side of the protein complex. We propose that the movement of the termini and the resulting negative surface form the basis for downstream signaling. Cyclic diguanosine monophosphate (c-di-GMP) is a ubiquitous bacterial second messenger that controls the switch from a single-cell lifestyle to surface-attached, multicellular communities called biofilms. PilZ domain proteins are a family of bacterial c-di-GMP receptors, which control various cellular processes. We have solved the solution structure of the Pseudomonas aeruginosa single-domain PilZ protein PA4608 in complex with c-di-GMP by NMR spectroscopy. Isotope labeling by 13C and 15N of both the ligand and the protein made it possible to define the structure of c-di-GMP in the complex at high precision by a large number of intermolecular and intraligand NOEs and by two intermolecular hydrogen bond scalar couplings. Complex formation induces significant rearrangements of the C- and N-terminal parts of PA4608. c-di-GMP binds as an intercalated, symmetric dimer to one side of the β-barrel, thereby displacing the C-terminal helix of the apo state. The N-terminal RXXXR PilZ domain motif, which is flexible in the apo state, wraps around the ligand and in turn ties the displaced C terminus in a loose manner by a number of hydrophobic contacts. The recognition of the dimeric ligand is achieved by numerous H-bonds and stacking interactions involving residues Arg8, Arg9, Arg10, and Arg13 of the PilZ motif, as well as β-barrel residues Asp35 and Trp77. As a result of the rearrangement of the N and C termini, a highly negative surface is created on one side of the protein complex. We propose that the movement of the termini and the resulting negative surface form the basis for downstream signaling. IntroductionThe second messenger cyclic diguanosine monophosphate (c-di-GMP) 5The abbreviations used are: c-di-GMP, cyclic diguanosine monophosphate; RDC, residual dipolar coupling; r.m.s., root mean square; r.m.s.d., root mean square deviation; NOE, nuclear Overhauser effect; ROE, rotating frame Overhauser effect. is widespread in and unique to the bacterial kingdom. Elevated intracellular levels of c-di-GMP generally cause bacteria to change from a motile single-cell state to an adhesive surface-attached multicellular state called biofilm (1Jenal U. Malone J. Annu. Rev. Genet. 2006; 40: 385-407Crossref PubMed Scopus (500) Google Scholar, 2Hengge R. Nat. Rev. Microbiol. 2009; 7: 263-273Crossref PubMed Scopus (1084) Google Scholar, 3Yan H. Chen W. Chem. Soc. Rev. 2010; 39: 2914-2924Crossref PubMed Scopus (40) Google Scholar). Moreover, c-di-GMP controls the virulence of animal and plant pathogens (4Cotter P.A. Stibitz S. Curr. Opin. Microbiol. 2007; 10: 17-23Crossref PubMed Scopus (249) Google Scholar, 5Dow J.M. Fouhy Y. Lucey J.F. Ryan R.P. Mol. Plant Microbe Interact. 2006; 19: 1378-1384Crossref PubMed Scopus (92) Google Scholar, 6Ryan R.P. Fouhy Y. Lucey J.F. Jiang B.L. He Y.Q. Feng J.X. Tang J.L. Dow J.M. Mol. Microbiol. 2007; 63: 429-442Crossref PubMed Scopus (131) Google Scholar, 7Tamayo R. Pratt J.T. Camilli A. Annu. Rev. Microbiol. 2007; 61: 131-148Crossref PubMed Scopus (365) Google Scholar, 8Malone J.G. Jaeger T. Spangler C. Ritz D. Spang A. Arrieumerlou C. Kaever V. Landmann R. Jenal U. PLoS Pathog. 2010; 6: e1000804Crossref PubMed Scopus (145) Google Scholar), progression through the cell cycle (9Duerig A. Abel S. Folcher M. Nicollier M. Schwede T. Amiot N. Giese B. Jenal U. Genes Dev. 2009; 23: 93-104Crossref PubMed Scopus (226) Google Scholar), antibiotic production (10Fineran P.C. Williamson N.R. Lilley K.S. Salmond G.P.C. J. Bacteriol. 2007; 189: 7653-7662Crossref PubMed Scopus (62) Google Scholar), and other cellular functions. In several pathogenic bacteria, c-di-GMP has been associated with the regulation of virulence factors and the development of chronic infections. During long term cystic fibrosis lung infections, increased persistence of Pseudomonas aeruginosa correlates with the generation of adaptive colony morphotypes. This includes mucoid colonies and small colony variants, auto-aggregative, hyper-adherent cells whose appearance correlates with poor lung function and persistence of infection. Both morphotypes are strongly linked to elevated levels of c-di-GMP, implicating a central role for this second messenger in chronic P. aeruginosa infections (8Malone J.G. Jaeger T. Spangler C. Ritz D. Spang A. Arrieumerlou C. Kaever V. Landmann R. Jenal U. PLoS Pathog. 2010; 6: e1000804Crossref PubMed Scopus (145) Google Scholar, 11Merighi M. Lee V.T. Hyodo M. Hayakawa Y. Lory S. Mol. Microbiol. 2007; 65: 876-895Crossref PubMed Scopus (255) Google Scholar, 12Drenkard E. Ausubel F.M. Nature. 2002; 416: 740-743Crossref PubMed Scopus (765) Google Scholar, 13Meissner A. Wild V. Simm R. Rohde M. Erck C. Bredenbruch F. Morr M. Römling U. Häussler S. Environ. Microbiol. 2007; 9: 2475-2485Crossref PubMed Scopus (91) Google Scholar, 14Hickman J.W. Tifrea D.F. Harwood C.S. Proc. Natl. Acad. Sci. U.S.A. 2005; 102: 14422-14427Crossref PubMed Scopus (577) Google Scholar). These studies emphasize the clinical significance of c-di-GMP and stress the importance for understanding c-di-GMP signaling in the pseudomonads.c-di-GMP comprises two guanosine monophosphate molecules that are symmetrically connected by 5′-3′ phosphodiester bonds, forming a 12-membered ring (see Fig. 1A). It is synthesized from two molecules of guanosine triphosphate (GTP) by diguanylate cyclases (GGDEF-containing domains) and hydrolyzed into the linear dinucleotide 5′-phosphoguanylyl-(3′-5′)-guanosine by the activity of c-di-GMP-specific phosphodiesterases (EAL-containing domains) (15Schirmer T. Jenal U. Nat. Rev. Microbiol. 2009; 7: 724-735Crossref PubMed Scopus (381) Google Scholar). The opposing activities of diguanylate cyclases and phosphodiesterases control the intracellular c-di-GMP concentrations, and hence c-di-GMP signaling. Several classes of c-di-GMP effector proteins have been identified so far, including PilZ domain proteins, response regulators, and degenerate GGDEF proteins that have lost catalytic activity (9Duerig A. Abel S. Folcher M. Nicollier M. Schwede T. Amiot N. Giese B. Jenal U. Genes Dev. 2009; 23: 93-104Crossref PubMed Scopus (226) Google Scholar, 16Christen M. Christen B. Allan M.G. Folcher M. Jenö P. Grzesiek S. Jenal U. Proc. Natl. Acad. Sci. U.S.A. 2007; 104: 4112-4117Crossref PubMed Scopus (149) Google Scholar, 17Lee V.T. Matewish J.M. Kessler J.L. Hyodo M. Hayakawa Y. Lory S. Mol. Microbiol. 2007; 65: 1474-1484Crossref PubMed Scopus (329) Google Scholar, 18Hickman J.W. Harwood C.S. Mol. Microbiol. 2008; 69: 376-389Crossref PubMed Scopus (461) Google Scholar, 19Krasteva P.V. Fong J.C. Shikuma N.J. Beyhan S. Navarro M.V. Yildiz F.H. Sondermann H. Science. 2010; 327: 866-868Crossref PubMed Scopus (307) Google Scholar). The PilZ protein family (named after the type IV pilus control protein in P. aeruginosa) represents the best studied class of effectors. Members of this family have been implicated in a diverse range of cellular functions including exopolysaccharide biosynthesis, flagellar motor activity, and virulence gene expression. However, little information is available about the mechanistic details involved in c-di-GMP-mediated PilZ activation of these cellular processes.Several structures of PilZ domain proteins have been solved in their apo and holo forms. One is the two-domain Vibrio cholerae protein VCA0042. A comparison of apo VCA0042 with its holo structure (20Benach J. Swaminathan S.S. Tamayo R. Handelman S.K. Folta-Stogniew E. Ramos J.E. Forouhar F. Neely H. Seetharaman J. Camilli A. Hunt J.F. EMBO J. 2007; 26: 5153-5166Crossref PubMed Scopus (176) Google Scholar) shows that binding of a single c-di-GMP molecule induces a conformational change in the loop connecting the C-terminal PilZ domain to the N-terminal YcgR-N domain. This brings the two domains into close proximity, thereby forming a new allosteric interaction surface with c-di-GMP at their mutual interface. It has been shown recently that YcgR, a homolog of VCA0042 in Escherichia coli, is able to bind to the flagellar motor in its c-di-GMP-bound form (21Boehm A. Kaiser M. Li H. Spangler C. Kasper C.A. Ackermann M. Kaever V. Sourjik V. Roth V. Jenal U. Cell. 2010; 141: 107-116Abstract Full Text Full Text PDF PubMed Scopus (338) Google Scholar). Although VCA0042 appears to bind only one molecule of c-di-GMP and does not alter its quaternary structure upon ligand binding, PP4397 from Pseudomonas putida binding of two molecules of c-di-GMP in the junction of its YcgR-N and PilZ domains results in a dimer-monomer transition (22Ko J. Ryu K.S. Kim H. Shin J.S. Lee J.O. Cheong C. Choi B.S. J. Mol. Biol. 2010; 398: 97-110Crossref PubMed Scopus (81) Google Scholar). This suggested that different PilZ domain proteins exhibit distinct binding stoichiometries and mechanistic principles.All structures of c-di-GMP protein complexes solved until today involve multidomain proteins (for review, see Ref. 15Schirmer T. Jenal U. Nat. Rev. Microbiol. 2009; 7: 724-735Crossref PubMed Scopus (381) Google Scholar). In these structures, the binding of c-di-GMP within a hinge-like region induces an allosteric rearrangement of the neighboring domains via fixation to the ligand. It was proposed that this c-di-GMP-induced domain immobilization represents a general mechanism for signal transduction. In contrast to these multidomain proteins, the PilZ domain PA4608 from P. aeruginosa is a single domain c-di-GMP-binding protein. The apo solution structure of PA4608 was solved by Ramelot et al. (23Ramelot T.A. Yee A. Cort J.R. Semesi A. Arrowsmith C.H. Kennedy M.A. Proteins. 2007; 66: 266-271Crossref PubMed Scopus (60) Google Scholar), who also confirmed binding of c-di-GMP by chemical shift analysis. NMR chemical shift mapping was then used to localize the ligand binding site of PA4608 to one side of the protein surface and to demonstrate that c-di-GMP binds to PA4608 as a dimer (16Christen M. Christen B. Allan M.G. Folcher M. Jenö P. Grzesiek S. Jenal U. Proc. Natl. Acad. Sci. U.S.A. 2007; 104: 4112-4117Crossref PubMed Scopus (149) Google Scholar). Furthermore, these analyses demonstrated that PA4608 remains monomeric after ligand binding (16Christen M. Christen B. Allan M.G. Folcher M. Jenö P. Grzesiek S. Jenal U. Proc. Natl. Acad. Sci. U.S.A. 2007; 104: 4112-4117Crossref PubMed Scopus (149) Google Scholar).Here we report the structure of the complex of PA4608 with c-di-GMP solved by advanced solution NMR techniques. Uniform 13C, 15N isotope labeling of both c-di-GMP and PA4608 allowed the observation of a large number of intermolecular and intraligand NOE contacts, 1DHN and 1DCH ligand and protein residual dipolar couplings (RDCs), and intermolecular hydrogen bond scalar couplings. Both termini of the protein undergo large structural changes upon ligand binding while retaining a certain amount of flexibility. In particular, the C-terminal helix is displaced by the ligand, thereby opening one side of the β-barrel as a binding site, and the N terminus containing the RXXXR PilZ domain motif wraps around the ligand and in turn ties the C-terminal helix in a loose conformation induced by a number of hydrophobic contacts. The rearranged termini expose a highly negatively charged surface on one side of the complex to a possible effector protein. This induced folding of the flexible N terminus containing the PilZ signature RXXXR and the resulting clustering of surface charges may present a general mechanism for c-di-GMP readout by PilZ domains. IntroductionThe second messenger cyclic diguanosine monophosphate (c-di-GMP) 5The abbreviations used are: c-di-GMP, cyclic diguanosine monophosphate; RDC, residual dipolar coupling; r.m.s., root mean square; r.m.s.d., root mean square deviation; NOE, nuclear Overhauser effect; ROE, rotating frame Overhauser effect. is widespread in and unique to the bacterial kingdom. Elevated intracellular levels of c-di-GMP generally cause bacteria to change from a motile single-cell state to an adhesive surface-attached multicellular state called biofilm (1Jenal U. Malone J. Annu. Rev. Genet. 2006; 40: 385-407Crossref PubMed Scopus (500) Google Scholar, 2Hengge R. Nat. Rev. Microbiol. 2009; 7: 263-273Crossref PubMed Scopus (1084) Google Scholar, 3Yan H. Chen W. Chem. Soc. Rev. 2010; 39: 2914-2924Crossref PubMed Scopus (40) Google Scholar). Moreover, c-di-GMP controls the virulence of animal and plant pathogens (4Cotter P.A. Stibitz S. Curr. Opin. Microbiol. 2007; 10: 17-23Crossref PubMed Scopus (249) Google Scholar, 5Dow J.M. Fouhy Y. Lucey J.F. Ryan R.P. Mol. Plant Microbe Interact. 2006; 19: 1378-1384Crossref PubMed Scopus (92) Google Scholar, 6Ryan R.P. Fouhy Y. Lucey J.F. Jiang B.L. He Y.Q. Feng J.X. Tang J.L. Dow J.M. Mol. Microbiol. 2007; 63: 429-442Crossref PubMed Scopus (131) Google Scholar, 7Tamayo R. Pratt J.T. Camilli A. Annu. Rev. Microbiol. 2007; 61: 131-148Crossref PubMed Scopus (365) Google Scholar, 8Malone J.G. Jaeger T. Spangler C. Ritz D. Spang A. Arrieumerlou C. Kaever V. Landmann R. Jenal U. PLoS Pathog. 2010; 6: e1000804Crossref PubMed Scopus (145) Google Scholar), progression through the cell cycle (9Duerig A. Abel S. Folcher M. Nicollier M. Schwede T. Amiot N. Giese B. Jenal U. Genes Dev. 2009; 23: 93-104Crossref PubMed Scopus (226) Google Scholar), antibiotic production (10Fineran P.C. Williamson N.R. Lilley K.S. Salmond G.P.C. J. Bacteriol. 2007; 189: 7653-7662Crossref PubMed Scopus (62) Google Scholar), and other cellular functions. In several pathogenic bacteria, c-di-GMP has been associated with the regulation of virulence factors and the development of chronic infections. During long term cystic fibrosis lung infections, increased persistence of Pseudomonas aeruginosa correlates with the generation of adaptive colony morphotypes. This includes mucoid colonies and small colony variants, auto-aggregative, hyper-adherent cells whose appearance correlates with poor lung function and persistence of infection. Both morphotypes are strongly linked to elevated levels of c-di-GMP, implicating a central role for this second messenger in chronic P. aeruginosa infections (8Malone J.G. Jaeger T. Spangler C. Ritz D. Spang A. Arrieumerlou C. Kaever V. Landmann R. Jenal U. PLoS Pathog. 2010; 6: e1000804Crossref PubMed Scopus (145) Google Scholar, 11Merighi M. Lee V.T. Hyodo M. Hayakawa Y. Lory S. Mol. Microbiol. 2007; 65: 876-895Crossref PubMed Scopus (255) Google Scholar, 12Drenkard E. Ausubel F.M. Nature. 2002; 416: 740-743Crossref PubMed Scopus (765) Google Scholar, 13Meissner A. Wild V. Simm R. Rohde M. Erck C. Bredenbruch F. Morr M. Römling U. Häussler S. Environ. Microbiol. 2007; 9: 2475-2485Crossref PubMed Scopus (91) Google Scholar, 14Hickman J.W. Tifrea D.F. Harwood C.S. Proc. Natl. Acad. Sci. U.S.A. 2005; 102: 14422-14427Crossref PubMed Scopus (577) Google Scholar). These studies emphasize the clinical significance of c-di-GMP and stress the importance for understanding c-di-GMP signaling in the pseudomonads.c-di-GMP comprises two guanosine monophosphate molecules that are symmetrically connected by 5′-3′ phosphodiester bonds, forming a 12-membered ring (see Fig. 1A). It is synthesized from two molecules of guanosine triphosphate (GTP) by diguanylate cyclases (GGDEF-containing domains) and hydrolyzed into the linear dinucleotide 5′-phosphoguanylyl-(3′-5′)-guanosine by the activity of c-di-GMP-specific phosphodiesterases (EAL-containing domains) (15Schirmer T. Jenal U. Nat. Rev. Microbiol. 2009; 7: 724-735Crossref PubMed Scopus (381) Google Scholar). The opposing activities of diguanylate cyclases and phosphodiesterases control the intracellular c-di-GMP concentrations, and hence c-di-GMP signaling. Several classes of c-di-GMP effector proteins have been identified so far, including PilZ domain proteins, response regulators, and degenerate GGDEF proteins that have lost catalytic activity (9Duerig A. Abel S. Folcher M. Nicollier M. Schwede T. Amiot N. Giese B. Jenal U. Genes Dev. 2009; 23: 93-104Crossref PubMed Scopus (226) Google Scholar, 16Christen M. Christen B. Allan M.G. Folcher M. Jenö P. Grzesiek S. Jenal U. Proc. Natl. Acad. Sci. U.S.A. 2007; 104: 4112-4117Crossref PubMed Scopus (149) Google Scholar, 17Lee V.T. Matewish J.M. Kessler J.L. Hyodo M. Hayakawa Y. Lory S. Mol. Microbiol. 2007; 65: 1474-1484Crossref PubMed Scopus (329) Google Scholar, 18Hickman J.W. Harwood C.S. Mol. Microbiol. 2008; 69: 376-389Crossref PubMed Scopus (461) Google Scholar, 19Krasteva P.V. Fong J.C. Shikuma N.J. Beyhan S. Navarro M.V. Yildiz F.H. Sondermann H. Science. 2010; 327: 866-868Crossref PubMed Scopus (307) Google Scholar). The PilZ protein family (named after the type IV pilus control protein in P. aeruginosa) represents the best studied class of effectors. Members of this family have been implicated in a diverse range of cellular functions including exopolysaccharide biosynthesis, flagellar motor activity, and virulence gene expression. However, little information is available about the mechanistic details involved in c-di-GMP-mediated PilZ activation of these cellular processes.Several structures of PilZ domain proteins have been solved in their apo and holo forms. One is the two-domain Vibrio cholerae protein VCA0042. A comparison of apo VCA0042 with its holo structure (20Benach J. Swaminathan S.S. Tamayo R. Handelman S.K. Folta-Stogniew E. Ramos J.E. Forouhar F. Neely H. Seetharaman J. Camilli A. Hunt J.F. EMBO J. 2007; 26: 5153-5166Crossref PubMed Scopus (176) Google Scholar) shows that binding of a single c-di-GMP molecule induces a conformational change in the loop connecting the C-terminal PilZ domain to the N-terminal YcgR-N domain. This brings the two domains into close proximity, thereby forming a new allosteric interaction surface with c-di-GMP at their mutual interface. It has been shown recently that YcgR, a homolog of VCA0042 in Escherichia coli, is able to bind to the flagellar motor in its c-di-GMP-bound form (21Boehm A. Kaiser M. Li H. Spangler C. Kasper C.A. Ackermann M. Kaever V. Sourjik V. Roth V. Jenal U. Cell. 2010; 141: 107-116Abstract Full Text Full Text PDF PubMed Scopus (338) Google Scholar). Although VCA0042 appears to bind only one molecule of c-di-GMP and does not alter its quaternary structure upon ligand binding, PP4397 from Pseudomonas putida binding of two molecules of c-di-GMP in the junction of its YcgR-N and PilZ domains results in a dimer-monomer transition (22Ko J. Ryu K.S. Kim H. Shin J.S. Lee J.O. Cheong C. Choi B.S. J. Mol. Biol. 2010; 398: 97-110Crossref PubMed Scopus (81) Google Scholar). This suggested that different PilZ domain proteins exhibit distinct binding stoichiometries and mechanistic principles.All structures of c-di-GMP protein complexes solved until today involve multidomain proteins (for review, see Ref. 15Schirmer T. Jenal U. Nat. Rev. Microbiol. 2009; 7: 724-735Crossref PubMed Scopus (381) Google Scholar). In these structures, the binding of c-di-GMP within a hinge-like region induces an allosteric rearrangement of the neighboring domains via fixation to the ligand. It was proposed that this c-di-GMP-induced domain immobilization represents a general mechanism for signal transduction. In contrast to these multidomain proteins, the PilZ domain PA4608 from P. aeruginosa is a single domain c-di-GMP-binding protein. The apo solution structure of PA4608 was solved by Ramelot et al. (23Ramelot T.A. Yee A. Cort J.R. Semesi A. Arrowsmith C.H. Kennedy M.A. Proteins. 2007; 66: 266-271Crossref PubMed Scopus (60) Google Scholar), who also confirmed binding of c-di-GMP by chemical shift analysis. NMR chemical shift mapping was then used to localize the ligand binding site of PA4608 to one side of the protein surface and to demonstrate that c-di-GMP binds to PA4608 as a dimer (16Christen M. Christen B. Allan M.G. Folcher M. Jenö P. Grzesiek S. Jenal U. Proc. Natl. Acad. Sci. U.S.A. 2007; 104: 4112-4117Crossref PubMed Scopus (149) Google Scholar). Furthermore, these analyses demonstrated that PA4608 remains monomeric after ligand binding (16Christen M. Christen B. Allan M.G. Folcher M. Jenö P. Grzesiek S. Jenal U. Proc. Natl. Acad. Sci. U.S.A. 2007; 104: 4112-4117Crossref PubMed Scopus (149) Google Scholar).Here we report the structure of the complex of PA4608 with c-di-GMP solved by advanced solution NMR techniques. Uniform 13C, 15N isotope labeling of both c-di-GMP and PA4608 allowed the observation of a large number of intermolecular and intraligand NOE contacts, 1DHN and 1DCH ligand and protein residual dipolar couplings (RDCs), and intermolecular hydrogen bond scalar couplings. Both termini of the protein undergo large structural changes upon ligand binding while retaining a certain amount of flexibility. In particular, the C-terminal helix is displaced by the ligand, thereby opening one side of the β-barrel as a binding site, and the N terminus containing the RXXXR PilZ domain motif wraps around the ligand and in turn ties the C-terminal helix in a loose conformation induced by a number of hydrophobic contacts. The rearranged termini expose a highly negatively charged surface on one side of the complex to a possible effector protein. This induced folding of the flexible N terminus containing the PilZ signature RXXXR and the resulting clustering of surface charges may present a general mechanism for c-di-GMP readout by PilZ domains.